2005
DOI: 10.1093/toxsci/kfi233
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Abnormal Accumulation of Fat Cells in the Rat Penis and Associated Loss of Fertility Depends upon Estrogen Exposure during Critical Period of Penile Development

Abstract: We previously reported that diethylstilbestrol (DES) or estradiol valerate (EV) exposure at a dose of 0.10-0.12 mg/kg, or higher, per day, on alternate days, from postnatal days 2-12, resulted in abnormal penis development and infertility (H. O. Goyal et al., 2005, J. Androl. 26, 32-43). The objective of this study was to identify a critical developmental period(s) during which EV exposure results in the observed penile abnormalities. Male pups received EV at a dose of 0.10-0.12 mg/kg on postnatal day(s) 1, 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 50 publications
5
41
1
Order By: Relevance
“…In agreement with our previous observations in the rat (Goyal et al 2005b), the weight of both penile skeletal muscles, bulbospongiosus and levator ani was not only significantly decreased but also was differentially decreased, with the former muscle undergoing a much higher decrease, as a result of neonatal estrogen exposure to wild-type mice. The mechanism of this differential decrease may lie in differences in androgen receptor concentration because both muscles are androgen dependent (Breedlove & Arnold 1983, Hadi Mansouri et al 2003 and, interestingly, both muscles are more developed in ERaKO mice than in wild-type/ control mice.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with our previous observations in the rat (Goyal et al 2005b), the weight of both penile skeletal muscles, bulbospongiosus and levator ani was not only significantly decreased but also was differentially decreased, with the former muscle undergoing a much higher decrease, as a result of neonatal estrogen exposure to wild-type mice. The mechanism of this differential decrease may lie in differences in androgen receptor concentration because both muscles are androgen dependent (Breedlove & Arnold 1983, Hadi Mansouri et al 2003 and, interestingly, both muscles are more developed in ERaKO mice than in wild-type/ control mice.…”
Section: Discussionsupporting
confidence: 92%
“…Although neonatal DES exposure in the present study did not significantly alter the adult level of plasma or intratesticular testosterone in wild-type mice, the neonatal level of intratesticular testosterone in rat pups treated with DES for 1-3 postnatal days was reduced by 90% at postnatal days 5-8 (Goyal et al 2005b), the developmental period when stromal cells start differentiation in the rat penis (Murakami 1986(Murakami , 1987, thus suggesting a role for estrogen-induced lower androgen action in inducing penile abnormalities by reprogramming stromal cell differentiation. In this context, observations that endogenous estrogens or DES exposure to fetal or neonatal Leydig cells decreased testosterone secretion in wild-type mice, but not in ERaKO mice, implied an ERa-mediated inhibitory role of estrogen in testosterone secretion (Delbes et al 2005).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Specifically, bisphenol A has been shown to accelerate terminal differentiation of 3T3L1 fibroblasts into adipocytes through the PI 3 kinse pathway [34]. Interestingly, in developmental studies, Goyal et al [35][36][37][38] have shown that administration of estradiol valerate or the estrogen receptor agonist diethylstilbestrol into 2-day-old rats resulted in infertile mature animals (120 d) and accumulation of fat-containing cells in the penile corpus cavernosum. In contrast, animals treated with vehicle exhibited no fat-containing cells and remained fertile.…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%